BMI in the Associations of Plant-Based Diets with Type 2 Diabetes and Hypertension Risks in Women: The E3N Prospective Cohort Study. Issue 9 (3rd June 2021) - Laouali, Nasser; Shah, Sanam; MacDonald, Conor-James; Mahamat-Saleh, Yahya; El Fatouhi, Douae; Mancini, Francesca; Fagherazzi, Guy; Boutron-Ruault, Marie-Christine
ABSTRACT: Background: Few studies have evaluated the quality of plant-based diets in relation to chronic diseases, and the potential role of BMI is not clearly explored. Objectives: To study the associations between plant-based diet indices and type 2 diabetes (T2D) and hypertension risks, as well as the extent to which the associations were modified and/or mediated by BMI. Methods: The study included 74, 522 women from the Etude Epidémiologique auprès de femmes de la Mutuelle Générale de l'Education Nationale prospective cohort [mean (SD): age, 52.94 (6.7) years; BMI, 22.970 (3.328) kg/m 2 ]. Dietary data were collected at baseline (1993) via an FFQ. Overall plant-based diet index (PDI), healthful PDI (hPDI), and unhealthful PDI (uPDI) were developed. Multivariable Cox regression models were used to derive HRs and 95% CIs. Effect modification and mediation by BMI were explored. Results: There were 3292 (4.64%) incident cases of T2D and 12, 504 (27.14%) incident cases of hypertension over ∼20 years of follow-up. In the multivariable model further adjusted for BMI, higher adherence to PDI and hPDI was associated with lower T2D and hypertension risks, with an HR per 1-SD increase (95% CI) of 0.88 (0.85, 0.91) and 0.96 (0.94, 0.98) for PDI and 0.88 (0.85, 0.92) and 0.94 (0.92, 0.95) for hPDI, respectively. uPDI was not associated with T2D [0.98 (0.94, 1.01)], whereas a positive association was observed with hypertension: 1.04 (1.02, 1.06). There was interaction between PDI and uPDI, as well as BMI, on T2D ( P -interaction < 0.001) but not on hypertension ( P -interaction > 0.05). In addition, BMI mediated 26–59% and 0.2–59% of diet–T2D and diet–hypertension associations, respectively. Conclusions: Differential associations between plant-based diets and T2D and hypertension risks were observed among women in this large prospective study. Only healthier plant foods were associated with lower risks, partly through decreasing BMI. The protocol was registered at clinicaltrials.gov as NCT03285230.